Computational hydrodynamics of capsules and biological cells - Pozrikidis, C. (Boca Raton,FL. : CRC Press, 2010)
'Preface Computational biofluiddynamics addresses a diverse family of problems involving fluid flow inside and around living organisms, organs and tissue, biological cells, and other biological materials. Numerical methods combine aspects of computational mechanics, fluid dynamics, computational physics, computational chemistry and biophysics into an integrated framework that couples a broad range of scales. The goal of this edited volume is to provide a comprehensive, rigorous, and current introduction into the fundamental concepts, mathematical formulation, alternative approaches, and predictions of computational hydrodynamics of capsules and biological cells. The book is meant to serve both as a research reference and as a teaching resource. Scope The numerical methods discussed in the following eight chapters cover a broad range of possible formulations for simulating the motion of rigid particles (platelets) and the flow-induced deformation of liquid capsules and cells enclosed by viscoelastic membranes. Although some of the physical problems discussed in different chapters are similar or identical, the repetition is desirable in that solutions produced by different numerical approaches can be compared and the efficiency of alternative formulations can be assessed. The consistency of the results validates the procedures and offers several alternatives.' Provided by publisher.
'A Chapman & Hall book.'
Includes bibliographical references and index.
Keywords: Body fluid flow -- Mathematical models; Fluid dynamics -- Mathematical models; Cells